Role of amino acids at positions 34, 296, and 486 of cytochrome P450 2D6 in the stimulatory and inhibitory effects of psychotropic agents on dopamine formation from p-tyramine. (2nd November 2021) - Niwa, Toshiro; Arima, Juri; Michihiro, Yurina
Abstract: The effects of psychotropic agents such as fluvoxamine, fluoxetine, paroxetine, milnacipran, and fluphenazine on dopamine formation from p -tyramine catalysed by cytochrome P450 (CYP) 2D6.2 (Arg296Cys;Ser486Thr), CYP2D6.10 (Pro34Ser;Ser486Thr), and CYP2D6.39 (Ser486Thr) were compared with the effects on dopamine formation from p -tyramine by CYP2D6.1. Michaelis constants ( K m ) and maximal velocity ( kcat ) values for dopamine formation and inhibition constants ( K i ) of the psychotropic agents were determined. For CYP2D6.39, the k cat values for fluvoxamine, fluoxetine, and milnacipran, but not for paroxetine and fluphenazine, gradually increased with increasing concentrations, indicating activation of the catalysed reaction. Fluphenazine competitively inhibited dopamine formation catalysed by all variants, with a higher K i value for CYP2D6.10. Among the three compounds that have a trifluoromethyl group in their chemical structure, only fluvoxamine and fluoxetine, as well as milnacipran that does not have this group, decreased K m values and/or increased k cat values for dopamine formation, suggesting that the group may not be essential for the activation. These findings indicate that substitution of amino acids at positions 34 and 486 can affect the affinity ( K m ) and enzymatic activity ( k cat ), respectively, for milnacipran and that the effect of substitution of arginine to cysteine at the 296 th position on the activation would be effector dependent.